Doenças respiratórias associadas à atividade de mineração no município de Parelhas, região do seridó norte-riograndense - Lima, Elisângela Maria de (2009)
This work aims to characterize the workers in mineral activities exposed to lung injuries in Parelhas Municipality, Rio Grande do Norte State, seeking to relate respiratory diseases to the mining activity. The studied area (Parelhas City), with about 19,700 inhabitants, is located in the Serido region, approximately 232 km far from Natal City. The number of people involved in informal mining activity (garimpo) in the Seridó region reaches about 5,000. These workers generally do not use any kind of individual protection equipments and develop, at early ages of greater productivity, severe forms of diseases, which end up disabling them to professional activities, family and social life. Deceases by respiratory problems (e.g. silicosis) have been reported in very young adults. A descriptive observational study was conducted based on information from the records found in Dr. José Augusto Dantas Hospital, between the years 1996- 2006. The occupational and socio-economic features of the population, which was selected by using the hospital records, were achieved through individually answered forms. The purpose was to link the occupational activities with the respiratory diseases. The next stage of the research was an observational case-control study, in the 1:1 proportion. The achieved data allowed confirming the central hypothesis of the research, which states that the pneumoconiosis cases are due to the mineral-based activities in the studied area. The final step of the investigation tried to assess the knowledge of relatives of students in public and private elementary and high schools from Parelhas City, regarding silicosis. About 15.4% of urban schools were analyzed through application of a structured questionnaire. The results show distinct socio-economic levels and a difference in the perception of the relatives of students in public and private schools, concerning silicosis. It was possible to identify the characteristics of the population economically involved with mineral-based activities and to define the group that deserves preferential attention in preventive actions. The work indicates some environmental problems caused by inadequate mining operations in the region